1994
DOI: 10.1210/jcem.78.4.8157720
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction reduces luteinizing hormone (LH) pulse frequency during waking hours and increases LH pulse amplitude during sleep in young menstruating women.

Abstract: To determine the effect of dietary energy restriction on gonadotropins, we assayed LH and FSH in samples drawn at 10- and 60-min intervals, respectively, over 24 h from seven young women (mean +/- SE gynecological age, 7.7 +/- 1.2 yr) on day 9, 10, or 11 of two menstrual cycles. Cortisol was measured in samples collected at 30-min intervals. During the 4 previous days and the day of sampling, dietary energy intake was set at either 45 or 10 Cal/kg lean body mass.day in random order. Beginning 2 days before tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
7

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 38 publications
4
48
0
7
Order By: Relevance
“…Partial restoration of leptin levels with r-metHuLeptin during 4-day fasting was associated with a decrease in overnight LH pulses in normalweight women, but fed-state leptin levels were not reached (23). Potential effects of r-metHuLeptin may have been obscured by interindividual differences, which our study and others (19,20,24,25) have minimized by studying the same subjects under different conditions at the same times of their menstrual cycles.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Partial restoration of leptin levels with r-metHuLeptin during 4-day fasting was associated with a decrease in overnight LH pulses in normalweight women, but fed-state leptin levels were not reached (23). Potential effects of r-metHuLeptin may have been obscured by interindividual differences, which our study and others (19,20,24,25) have minimized by studying the same subjects under different conditions at the same times of their menstrual cycles.…”
Section: Discussionmentioning
confidence: 53%
“…Although follicle development was not directly evaluated, the maintenance of normal menstrual cycles argues against substantial disruption of follicular growth and ovulation. Interestingly, normal-weight women have decreased LH pulse frequency during short-term starvation despite maintaining ovulatory cycles in several (19,20) but not all (21-23) studies. Partial restoration of leptin levels with r-metHuLeptin during 4-day fasting was associated with a decrease in overnight LH pulses in normalweight women, but fed-state leptin levels were not reached (23).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some data suggested that no relationship existed between body fat and reproduction, since no differences in adiposity were noted between eumenorrheic and amenorrheic female runners [32,51]. However, a close association was shown between a disturbed sex hormonal profile and low energy availability (energy intake reduced by energy expenditure) in women who engaged in strenuous physical activity [31,34,63]. Interestingly, deteriorations in the LH and FSH secretions similar to those observed in female athletes were observed in sedentary women with eating disorders, such as bulimia nervosa [29,49].…”
Section: History Of Exercise -The Female Athlete Triad Connectionmentioning
confidence: 99%
“…Estima-se que a ocorrência de amenorréia exista em 30 a 50% das bailarinas profissionais, 50% das corredoras competitivas, 25% das corredoras não competitivas e 12% das nadadoras e ciclistas. Ginastas, tendo seu estado nutricional avaliado, demonstraram baixo percentual de gordura e retardo no aparecimento dos caracteres sexuais (82,83). É importante ainda destacar estudos prospectivos que demonstraram a existência de alterações ovulatórias subclínicas em mulheres que praticam exercícios de forma recreativa.…”
Section: Leptina Exercício E Amenorréia Do Esforçounclassified